2020
DOI: 10.1002/jlcr.3875
|View full text |Cite
|
Sign up to set email alerts
|

Thorium chelators for targeted alpha therapy: Rapid chelation of thorium‐226

Abstract: One of the main challenges in targeted alpha therapy is assuring delivery of the α‐particle dose to the targeted cells. Thus, it is critical to identify ligands for α‐emitting radiometals that will form complexes that are very stable, both in vitro and in vivo. In this investigation, thorium‐227 (t1/2 = 18.70 days) chelation of ligands containing hydroxypyridinonate (HOPO) or picolinic acid (pa) moieties and the stability of the resultant complexes were studied. Chelation reactions were followed by reversed‐ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…A comparative study of chelating agents containing HOPO or picolinic acid (pa) moieties was recently reported for possible complexation of 226 Th. Chelation properties of octadentate HOPO ligands were confirmed and octadentate or undecadentate pa ligands appeared as potential chelators for thorium by demonstrating high radiolabeling yields and interesting stability of the corresponding complexes [ 293 ].…”
Section: Thorium-227mentioning
confidence: 99%
“…A comparative study of chelating agents containing HOPO or picolinic acid (pa) moieties was recently reported for possible complexation of 226 Th. Chelation properties of octadentate HOPO ligands were confirmed and octadentate or undecadentate pa ligands appeared as potential chelators for thorium by demonstrating high radiolabeling yields and interesting stability of the corresponding complexes [ 293 ].…”
Section: Thorium-227mentioning
confidence: 99%
“…A few such examples of these are 226 Th (t 1/2 = 30.57 min), which decays by multiple successive alpha emissions to long-lived 210 Pb [82], and the beta-minus emitter 214 Pb (t 1/2 = 27.06 min) and its succession of beta and alpha emitting daughter isotopes [83]. For both radionuclides, integration of the parent isotope, i.e., 230 U (t 1/2 = 20.23 d) for 226 Th and 222 Rn (t 1/2 = 3.82 d) for 214 Pb, into a generator form is a key feature that makes dispensation, tagging, and administering of the end drug possible despite the shorter than usual half-lives [84].…”
Section: Technetium-101 As a Potential Ephemeral Diagnostic Therapeutic And/or Theranostic Agentmentioning
confidence: 99%
“…They found that these chelators could retain high chelation yields with thorium-227 within 2.5 h or less. The thorium complexes possess high stability in phosphate-buffered saline at ambient condition over a 6-dayperiod [143].…”
Section: Common Bifunctional Chelators and Hopo-based Bifunctional Chelators For 227 Thmentioning
confidence: 99%